Aspekty procesowe nałożenia przez Prezesa Urzędu Regulacji Energetyki kary pieniężnej. Wybrane zagadnienia - Hyżorek, Aleksander (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The considerations of this article focus on the energy law sector, in particular, expenditure sanctions by the President of the Energy Regulatory Office. The article points to the current regulation related to the subject of fines in the energy sector and presented de lege ferenda postulates. The ratio legis of the proposed changes aimed at the unification of the proceedings before the President of the Energy Regulatory Office is also discussed. Reference is also made to the procedural aspects of the proceedings.
Keywords: financial penalties in the energy sector; appeal against the decision of the President of the Energy Regulatory Office; the President of the Energy Regulatory Office; administrative law; procedural aspects